Empirical Scenarios of Emission Control and Economic Sustainability for Energy Input and Intervention of Agricultural Pesticides - Qosim, Ahmad; Anies, Anies; Sunoko, Henna Rya (International Journal of Energy Economics and Policy, 2019)
The application of pesticides have been out of control, therefore, it is damaging environment due to emissions of vary substances and gases, e.g. CO2, SO2, PO4, and Summer Smog. This negative impact alone is also going to affect the paddy production. A comprehensive measure must be taken in order to create a sustainable development in agricultural sectors. Control on pesticides is one of the best practices to be proposed. This study used a quantitative methodology with a Life Cycle Assessment approach to test empirically the use of pesticides and to propose various scenarios in the effort of modification of environmentally friendly and low emission agriculture, which includes aspects of Greenhouse, Acidification, Eutrophication, SPM Smog. By using Life Cycle Assessment with quantitative measurement using SimaPro 7, the findings show that ratio of emission rate of the existing condition to the proposed model proved a 34.5% decrease in CO2 equivalent (136.4 kg) and 41.6% decrease in SO2. As the environmental risks decreases, it is expected that the sustainable agricultural development of paddy commodity can be materialised. Some recommendations are given by the researc findings, i.e. distribution system according to the proposed model, recording, monitoring, and legal enforcement towards the sustainable development. Keywords: Paddy, Pesticide Control, Agricultural Sustainability, Emission JEL Classifications: K32, O13, P18 DOI: https://doi.org/10.32479/ijeep.7687